Intrauterine device is embraced by the placenta - Yared, Georges J.; Al Hasan, Jihad M.; El Hajjar, Charlotte A.; Ghazal, Kariman S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
The intrauterine device (IUD) is a contraceptive method which are tiny, T-shaped plastic, that is placed within the uterus and left there, is used all throughout the world with more than 99% effectiveness rate. Pregnancy with a levonorgestrel-releasing intrauterine system (LNG-IUS) in situ is very rare. Intracavitary pregnancy with an IUD can lead to a higher risk of infection and preterm birth. We described a case of a live birth with an IUD inserted into the placenta. A 27-year-old Syrian woman in G4P3 with a history of healthy vaginal deliveries arrived in our delivery room at 39+3 weeks gestation complaining of labor pain A vaginal examination revealed bulging membranes and a fully dilated cervix. She delivered a live baby boy, weighing 3100 g and being sent to the nursery with an APGAR score of 9 to 10. When the placenta was examined, a white foreign object that was embedded there was discovered to be an intrauterine device. Although intrauterine pregnancy is a potential problem that must be taken into account, ectopic pregnancy is a reasonably common complication of intrauterine contraceptive devices. Although several studies have shown that term pregnancies with excellent prognoses can occur after the removal of intrauterine devices, close monitoring is necessary to detect misplaced copper-T and prevent undesired births.